2021
DOI: 10.3389/fclim.2020.584245
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Preparedness for Building Resilient Agri-Food Systems: Lessons From the 2015/2016 El Niño Drought in Malawi

Abstract: Across sub-Saharan Africa, climate change is leading to increasingly erratic weather patterns that challenge farming practices, particularly for smallholder farmers. Preparing farmers for these changes and increasing their resilience to extreme weather events is critical for food security in areas where populations are increasing. The El Niño event of 2015/16 led to drought conditions in Malawi which are expected to become more normal in the future. This resulted in widespread crop failure and the need for ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Our studies in Malawi and Tanzania form part of the GCRF-AFRICAP (Agricultural and Food-System Resilience: Increasing Capacity and Advising Policy) project. In Malawi, research was co-designed building on past studies evaluating Conservation Agriculture (CA), which identified institutional needs [12], community priorities for climate resiliencebuilding projects [13], and the ability for CA to enhance maize yield resilience to heat stress [14], dry spells [15] and drought when agricultural extension and village health systems empower farming communities [16,17]. In Tanzania, our studies focus on evaluating Climate-Smart Agriculture initiatives in the East Usambara mountains where climate-smart management practices on highland farms have been promoted as part of the European Union's Global Climate Change Alliance (GCCA+) integrated adaptation programme [18].…”
Section: Methodsmentioning
confidence: 99%
“…Our studies in Malawi and Tanzania form part of the GCRF-AFRICAP (Agricultural and Food-System Resilience: Increasing Capacity and Advising Policy) project. In Malawi, research was co-designed building on past studies evaluating Conservation Agriculture (CA), which identified institutional needs [12], community priorities for climate resiliencebuilding projects [13], and the ability for CA to enhance maize yield resilience to heat stress [14], dry spells [15] and drought when agricultural extension and village health systems empower farming communities [16,17]. In Tanzania, our studies focus on evaluating Climate-Smart Agriculture initiatives in the East Usambara mountains where climate-smart management practices on highland farms have been promoted as part of the European Union's Global Climate Change Alliance (GCCA+) integrated adaptation programme [18].…”
Section: Methodsmentioning
confidence: 99%
“…International cooperation in food security, such as the APTERR, is essential for addressing global food security and climate resilience Kim, 2021). Evaluating climate-smart agriculture is crucial for building climate resilience in African food systems (Dougill et al, 2021). Additionally, farmer preparedness is vital for building resilient agri-food systems, as demonstrated in the context of the 2015/2016 El Niño drought in Malawi (Mkwambisi et al, 2021).…”
Section: Collaborative Strategies For Enhanced Adaptation and Sustain...mentioning
confidence: 99%
“…Therefore, variations in weather and weather extreme events frequently damage crops, and farmers do not take any precautionary measures. 12,13 Moreover, the benefit of favorable weather events (e.g. fertilizer application on a sunny day or reduction of irrigation for the next hours/days of rainfall) remains unexploited.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, farmers cultivate in a weather‐blind situation for subsequent hours. Therefore, variations in weather and weather extreme events frequently damage crops, and farmers do not take any precautionary measures 12,13 . Moreover, the benefit of favorable weather events (e.g.…”
Section: Introductionmentioning
confidence: 99%